2008
DOI: 10.1007/s00381-008-0717-2
|View full text |Cite
|
Sign up to set email alerts
|

Paravertebral malignant tumors of childhood: analysis of 28 pediatric patients

Abstract: Majority of cases presented with advanced disease. Late referral is the major cause of morbidity and mortality. The CC caused by PMTs should be initially managed with corticosteroids +/- chemotherapy to avoid the adverse late effects of RT and surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…[ 14 15 16 ] However, if there is unusual presentation of the paraspinal lesions, based only on imaging, there may be a difficulty in making a correct preoperative diagnosis. [ 17 18 19 ] The differential diagnosis of extensive paraspinal soft tissue and adjacent include malignant tumors, metastasis, pyogenic and fungal infections, sarcoidosis, and rarely paraspinal tuberculosis. [ 1 20 ] The management of paraspinal lesions is aimed to confirm the diagnosis, either fine needle aspiration cytology or preferably by complete surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 15 16 ] However, if there is unusual presentation of the paraspinal lesions, based only on imaging, there may be a difficulty in making a correct preoperative diagnosis. [ 17 18 19 ] The differential diagnosis of extensive paraspinal soft tissue and adjacent include malignant tumors, metastasis, pyogenic and fungal infections, sarcoidosis, and rarely paraspinal tuberculosis. [ 1 20 ] The management of paraspinal lesions is aimed to confirm the diagnosis, either fine needle aspiration cytology or preferably by complete surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…For the neuroblastoma survivors, their fit-for-service frequency was 57%, and the highest proportion of survivors (50%) qualified for the best fitness category was among them. Neuroblastoma survivors may have motor or sensory deficits, and spinal cord compression may complicate neurological functions and thereby decrease physical capacity [21]. It could be assumed that most neuroblastoma survivors fit-for-service were those treated for stage I and II diseases or even stage IVS and were thus not exposed to long chemotherapies or irradiation treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Güneş et al, in a study of 28 children with primary paravertebral tumors, reported that the majority of tumor diagnoses were neuroblastoma (46.4 %), and soft tissue sarcoma (35.7%). [10] Because a variety of unusual lesions have radiological features similar to paravertebral tumors, in the case of a paravertebral mass, a diagnosis other than malignant tumor should be considered, including tuberculosis, especially in endemic areas. In conclusion, this case highlights the importance of being aware that spinal tuberculosis has many different radiographic features and can mimic a spinal malignancy.…”
Section: Discussionmentioning
confidence: 99%